Pengaruh Kombinasi Media Lapisan Tanah dan Takaran Cocopeat pada Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Eko Saputra; Rijadi Subiantoro; Adryade Reshi Gusta (Politeknik Negeri Lampung, 2019)
Efforts to produce good quality cocoa seedling in quality and quantity, ie the use of planting media containing nutrients needed by plants. Topsoil and cocopeat combination are expected to increase the growth of cocoa seedling. The purpose of this study was to to obtain a good soil layer medium planting on the growth of cocoa seedling, to obtain optimum cocopeat on the growth of cocoa seedling, and to obtain the interaction of soil layer medium planting and cocopeat on the growth of cocoa seedlings. This research was conducted in PoliteknikÂ Negeri Lampungâ€™s Teaching Farm in January 2017 until June 2017. The experiment was conducted by factorial randomized block design with two factors and each treatment combination was repeated 3 times. The first factor consists of two levels and the second factor consists of four levels. The first factor, namely top soil and sub soil. The second factor is composting cocopeat on planting medium consisting of 0% cocopeat and 100% soil, 25% cocopeat and 75% soil, 50% cocopeat and 50% soil, 75% cocopeat and 25% soil. The results showed that the cocopeat 0%-75% gave the same effect on the high varieties of seedlings, stem diameter, number of leaves, total dry weight, and dry root weight. In general, top soil and sub soil medium planting did not affected on the growth of cocoa seedling and cocopeat did not affected on the growth of cocoa seedling. There was no interaction between media layer of soil and cocopeat in all observation variables.Â